Associations between change in blood pressure and functional outcome, early events and death: results from the Efficacy of Nitric Oxide in Stroke trial. Issue 10 (October 2019) - Sandset, Else C.; Appleton, Jason P.; Berge, Eivind; Christensen, Hanne; Gommans, John; Krishnan, Kailash; Ntaios, George; Phillips, Stephen; Pocock, Stuart; Sprigg, Nikola; Woodhouse, Lisa J.; Bath, Philip M.
Abstract : Objectives: High blood pressure (BP) is associated with a poor outcome after acute stroke. Early reduction in BP may be associated with fewer early adverse events and deaths, and improved functional outcome. Methods: Analyses used data from the Efficacy of Nitric Oxide in Stroke trial, a multicentre randomized single-masked and outcome-masked trial of glyceryl trinitrate vs. no glyceryl trinitrate in 4011 patients recruited within 48 h of an ischaemic or haemorrhagic stroke and with raised SBP (140–220 mmHg). Change in SBP from baseline to day 1 was categorized as: more than 15% decrease, 15–5% decrease, 5% decrease to 5% increase (no change – reference) and more than 5% increase. The primary outcome was functional outcome (modified Rankin scale) score at 90 days. Results: Across all patients, both moderate (5–15%) and large (>15%) decreases in SBP were associated with beneficial shifts in the modified Rankin scale relative to patients with no change in BP: adjusted common odds ratio (OR) 0.81 [95% confidence interval (CI) 0.70–0.90] and OR 0.84 (95% CI 0.71–1.00), respectively. A moderate decrease in SBP was also associated with a lower risk of early adverse events, adjusted OR 0.69 (95% CI 0.52–0.90). Conclusion: Modest decreases in SBP in acute stroke appear to be associated with fewer early events and better long-term functional outcome.